Students’ Career Understanding and Career Decision Making Self-Efficacy in Junior High School - Akhsania, Khayatun Nufus; Basuki, Tentrem; Sugiharto, DYP; Japar, Muhammad (Islamic Guidance and Counseling Journal, 2021)
This study aimed to determine students’ career understanding on the career decision making self-efficacy of Junior High School students in Central Java Province. The study used qualitative method, comparative test for data analysis, and self-efficacy scale to collect the career decision making data of students who have and have not gained career understanding. In this way, Bandura’s theory of self-efficacy was used as a framework theory, while cluster random sampling was employed to collect the study sample (N = 311). The data collection was done through a direct survey using 25 questions regarding career decision making self-efficacy (CDSE-SF) and career understanding questionnaire. Based on the data analysis, the researchers found significant differences in CDSE-SF results of students who have gained career understanding and not, including (1) Understanding of various alternative jobs (t(311) = 4.911, p < .000), (2) Information on the world of work requirements (t(311) = 4.602, p <.000), (3) Information on job vacancies (t(311) = 4.111, p < .000), and (4) Understanding of job qualifications (t(311) = 3.460, p < .001). These findings recommend the students to improve their career decision making using career guidance and counseling strategies in form of various alternative services, such as career counselling services, group guidance, classroom service, and even support from other parties.